Ethnic Distinctions, Legal Connotations: Chinese Patterns of Boundary Making and Crossing - Lee, Byung Ho (SAGE Open, 2021)
This study analyzes, from a comparative and historical perspective, the clash between state statutory law and native customary law and the consequential effects of that rivalry on ethno-legal categories. It adopts a long-term perspective on Chinese society, with a particular focus on its history over the last three centuries. Although the imperial Chinese state had a centralized legal code, many non-Han subjects followed different legal standards and systems. Such conditions became the basis of legal pluralism and the structural constraint for full-fledged legal uniformity. It is argued that state-imposed ethnic categories in China have been institutionalized to determine those who should be protected, or even privileged, by their own native law. This is especially true during the alien dynasties of conquest, which purposely emphasized the principle of personal law to preserve legal prerogatives of ruling ethnicity. Similarly, indigenes on the frontier carried a variety of legal exemptions on grounds of the principle of territorial law. Such conditions could leave room for individual agency and provide incentives for both acculturated Han settlers and sinicized indigenes to claim native status. Several examples, including an 18th-century homicide case in China’s southwestern frontier, substantiate how individuals manipulated their ethnicity for their self-advantage and how these behaviors complicated the personality and territoriality principles of imperial law. In this sense, ethnic law served as an institutionalized distillation of ethnic group boundaries, which were realigned by shifts in self-identity. The legacy of China’s imperial practices of particularistic jural relations continues today.
Keywords: boundary-crossing; boundary-making; China; empire; ethnicity; frontier society; legal pluralism; native chieftaincy